Effect of Fabric Pattern and Color on Impression Evaluation of Textile Images Rendered by a Textile Simulator (Journal of Fiber Bioengineering and Informatics, 2016)
The expression ability of a commercial textile simulator was investigated by simulating textile imagestaking into account the effect of yarn count, weave density, yarn types and weave. The performance ofthe simulator was investigated by evaluating and comparing impressions of real textiles and simulatedimages. The effect of pattern and textile color on the simulation performance was also studied. It wasfound that simulated images of textiles with more complicated and multicolored patterns were perceivedto be more alike to the real textiles. Simulated images with large patterns were also evaluated andfound to compare favorably to real textiles. Color was observed to have no effect on the impression ofsimulated textile images. Therefore, textile simulation in the textile trade is more effective on complexvariations of textile patterns and colors.
Keywords: Performance; Textile Image; Textile Simulation; Color and Pattern